Urogenital Colonization and Characterization of Extended Spectrum Beta-Lactamase-Producing Gram-Negative Isolates From Infertile Women at Selected Hospitals in Ibadan, Nigeria (African Journal of Biomedical Research, 2023)
Antimicrobial resistance as a result of Extended Spectrum Beta-Lactamase production among Gram- negative bacteria to commonly prescribed antibiotics is increasing all over the world. ESBL production among urinary-pathogens may predispose women to treatment failure as a result of resistance to antibiotics and increases the risk for various reproductive dysfunctions that can precipitate infertility.In this study, ESBL-producing gram negative isolates from urine and high vaginal swab of infertile women were investigated for a period of one year (2020 and 2021). Urine and high vaginal swabs were taken from 140 infertile women (mean age of 26 and 33) for cases of primary and secondary infertility respectively. Standard microbiological analysis including microscopy, culture and sensitivity using the VITEK-2 automated compact system and disk diffusion method were employed. Detection of ESBL phenotypes among the isolates was conducted using double disc synergy test.Klebsiella pneumoniae, Escherichia coli and Pseudomonas aeruginosa were identified as follows and in this respective proportion (72%, 64%, 43%) with Klebsiella pneumoniae being the most prevalent. ESBL-production was detected in 62.9% of isolates with multi-drug resistance potential. The overall prevalence of Carbapenem sensitivity was high for all isolates except for Escherichia coli with 50% resistance expressed. Infertile women had a significant colonization of ESBL-producing pathogen in their urinary tract, may suffer the risk of transmission of infection to the reproductive tract; an important risk factor for reproductive dysfunctions to be addressed. These findings emphasized the need to embrace regular periodic surveillance of antimicrobial resistance and access to molecular screening towards treatment of bacterial infections